(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Logvinenko A.Y. Using interactive teaching methods to prepare future teachers of foreign language tolerant communication activities. The article is devoted to consideration of interactive methods of teaching and their role to the tolerant communicative activity in the process of future foreign language teachers’ training. The examples of interactive forms that favor development of communicative and creative skills, tolerant attitude to representatives of other nations while teaching English are shown.